The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1108/jices-06-2022-0059
|View full text |Cite
|
Sign up to set email alerts
|

Social punishment by the distribution of aggressive TikTok videos against women in a traditional society

Abstract: Purpose Online violence has been rampant in the past decade, intensifying the victims’ suffering owing to its rapid dissemination to vast audiences. This study aims to focus on online gender-based violence directed against young Bedouin women who have left their male-dominated home territory for academic studies. This study examined how the backlash against these students, intended to stop changes in traditional gender roles, is reflected in offensive TikTok videos. Design/methodology/approach This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The second strategy dealt with addressivity of the texts; that is, it clarified to whom the writers were addressing their message (Ben-Atar et al , 2023). We found that 84% of the texts talked “about” the Bedouin women, without directly addressing them: “I pity them; what a cruel world!…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second strategy dealt with addressivity of the texts; that is, it clarified to whom the writers were addressing their message (Ben-Atar et al , 2023). We found that 84% of the texts talked “about” the Bedouin women, without directly addressing them: “I pity them; what a cruel world!…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the online comments showed that the response discourse was not expected to open a discussion: rather, the writers made proclamations. Research of online comments teaches us about “bottom-up” communication – a kind of communication that has grown in popularity in communication studies in recent years (Ben-Atar et al , 2023). The commentators neither belong to a group with a common identity, nor are they community agents: they write only in their name.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, traditional societies often imposed strict codes of conduct and morality on women. These codes were deeply rooted in cultural beliefs and were aimed at maintaining social order and stability (Ella et al, 2023). Women were expected to adhere to social norms and behave in ways that were deemed "respectable" by society.…”
Section: "Up To the Day Of Her Death At Seventy-four It Was Still Tha...mentioning
confidence: 99%